The effect of a deep learning strategy on developing print design skills for students of the Department of Art Education (Journal of the College of Basic Education, 2022)
The research aimed to know the effect of the deep learning strategy in developing print design skills among students of the Department of Art Education, and to test the goal of the research, the researcher formulated the null hypothesis, which stated that there is no statistically significant difference at the level of significance (0.05) between the average degrees of achievement of the members of the research sample. Those who are exposed to the deep learning strategy and the average achievement scores of the research sample members who are exposed to the traditional method in the post-test in print design skills. The researcher adopted the experimental design with partial control, for its suitability for the purposes of the current research, so two groups were designed, the first is an experimental group subject to the deep learning strategy, and the second is a control group that is not exposed to anything and lessons are presented in the traditional way in it. The experiment sample consisted of (60) male and female students who were distributed Randomly into two experimental and control groups of (30) male and female students in each group, and the researcher conducted equivalence in a number of variables between the experimental and control groups, then the researcher applied the experiment based on the deep learning strategy and then conducted a post-print design skills test, and reached the following result: There are statistically significant differences in the performance of the experimental and control groups on the print design skills test, meaning that there is a difference in favor of students who follow the deep learning strategy through their performance on the post test.Then the researcher developed a set of conclusions, recommendations and suggestions.